Determination of competitiveness of coal is on the cost of use fuel heat - Kateryna Pilova (Cхід, 2013)
Economic and technological feasibility of use in energy-rich fuel is justified. An approach to adjustment the price of coal, that provides a record heat and power fuel properties and provides an opportunity to determine the indicators of coal competitiveness in the market of primary resources is identified.